Mechanistic elucidation guided by covalent inhibitors for the development of anti-diabetic PPARγ ligands. Issue 8 (26th May 2016) - Bae, Hwan; Jang, Jun Young; Choi, Sun-Sil; Lee, Jae-Jin; Kim, Heejun; Jo, Ala; Lee, Kong-Joo; Choi, Jang Hyun; Suh, Se Won; Park, Seung Bum
Abstract : We revealed the X-ray structure of PPARγ co-crystallized with SR1664 bound to the alternate binding site of PPARγ and confirmed that this blocks the phosphorylation of Ser273. Abstract : Peroxisome proliferator-activated receptor gamma (PPARγ) is a ligand-regulated transcription factor that plays crucial roles in adipogenesis, lipid metabolism, and glucose homeostasis. Several PPARγ ligands possess anti-diabetic activity and they commonly inhibit the phosphorylation of PPARγ at serine 273 (Ser273). The recently reported PPARγ ligand SR1664, which selectively blocks the phosphorylation of PPARγ without classical agonism, has potent anti-diabetic activity, indicating that the inhibition of Ser273 phosphorylation is sufficient to provoke anti-diabetic effects. In this study, we revealed the X-ray structure of PPARγ co-crystallized with SR1664 bound to the alternate binding site of PPARγ and confirmed that the alternate site binding of SR1664 blocks the phosphorylation of Ser273. Furthermore, using covalent inhibitors as chemical tools, we demonstrated that the inhibition of phosphorylation is attributed to the occupation of a specific site which is a hydrophobic region between helix 3 and β3–β4 at the binding pocket of PPARγ. In high-fat diet-induced obese mice, we confirmed the anti-diabetic activity of our covalent inhibitor SB1453 that was designed to bind at the specific site in PPARγ for blocking the phosphorylation of Ser273. Lastly, the target selectivity of SB1453 was demonstrated by fluorescence-based visualization of target proteins complexed with the covalent probe11 containing a bioorthogonal functional group.